International Liability When Violating the Headquarters of Diplomatic Missions (المجلة الدولية للبحوث العلمية, 2024)
The development of international relations has made most countries of the world rely on diplomatic representation in all its forms as a means of communication and protection of mutual interests. The diplomatic mission is the link between the governments of the countries that are working to achieve cooperation starting from the transfer of different opinions between countries and trying to overcome the difficulties that escape the entanglement Interests.The Diplomatic Mission has given its diplomatic and diplomatic functions to the diplomatic missions a special status, with full protection, so that it can play its role quietly away from all pressures, In the State which has adopted it. This reality is found in peacetime when States have ratified the Vienna Convention on Diplomatic Relations, 1961.In times of war, if we accept the severance of diplomatic relations because of a war between two countries exchanging diplomatic representation, States must apply the rules of international humanitarian law and consider diplomatic envoys among the civilians recognized by the Fourth Geneva Convention of 1949 as special protection against the enemy state, And the role and headquarters of diplomatic missions should be classified as civilian objects that should not be the target of military operations.To establish and maintain international protection for diplomatic missions and to establish mechanisms for this, namely, the establishment of international responsibility for the violation of the inviolability of the diplomatic envoy and the role of diplomatic missions, there is a tortious responsibility by the receiving State as it did not provide security for the diplomatic mission, Executive or judicial authority. The personal criminal responsibility of the President for his acts or those of his subordinates is also carried out If a serious violation of the Fourth Geneva Convention of 1949 is committed.